Factors Affecting Early Marriage in Dau District, Malang Regency - Tiyaningsih, Agus; Frety, Endyka Erye; Amalia, Rize Budi; Prasetyo, Budi (Preventia: The Indonesian Journal of Public Health, 2024)
Indonesia still in 8th largest early marriage rate in the world. Many factors cause early marriage to occur, therefore this study aims to analyze the factors that influence early marriage in Dau District, Malang Regency. To analyze the factors that influence early marriage in Dau District, Malang Regency. The design of this study was observational analytic use Cross Sectional approach. The population in this study were women who married in 2022 in Dau District of Malang Regency, amount 511 women and the sample were 60 women. The independent variables in this study are education, family income, surrounding cultural beliefs, peers, knowledge, attitudes and mass media, while the dependent variable is early marriage. Data analysis of the results of this study used bivariate analysis with Chi-Square statistical test and multivariate analysis with logistic regression test. The results of the study showed that there was associated between variables of education (p value 0.00), peers (p-value 0.008), and attitude (p value 0.023) with the incidence of early marriage and the most variable affecting incidence of early marriage is education.